Overnight Shift From Obstructive to Central Apneas in Patients With Heart Failure - Ružena Tkáčová; Mitra Niroumand; Geraldo Lorenzi‐Filho; T. Douglas Bradley (2001)
Background —Obstructive (OSA) and central sleep apnea (CSA) can coexist in patients with congestive heart failure (CHF). However, the reason why OSA events occur at one time and CSA events at another has not been determined. We hypothesized that a change in P co 2 would be associated with an alteration in apnea type: a decrease in P co 2 should lead to CSA. Methods and Results —To test this hypothesis, we evaluated minute ventilation (V I ), transcutaneous P co 2 (Ptc co 2 ), circulation time, and periodic breathing cycle length during overnight polysomnography in 12 patients with CHF and coexisting OSA and CSA. V I was significantly greater (mean±SEM, 9.4±1.3 versus 8.0±0.9 L/min; P <0.05) and Ptc co 2 was lower (39.4±1.0 versus 41.9±1.1 mm Hg, P <0.01) during episodes of CSA than of OSA. These changes were associated with significant lengthening of circulation time (23.6±3.7 versus 21.1±3.6 seconds, P <0.01) and periodic breathing cycle length (53.7±3.5 versus 49.6±2.9 seconds, P <0.01). In addition, the proportion of obstructive events decreased (from 68.5±11.4% to 22.5±7.2%, P <0.001) and of CSA events increased (from 31.5±11.4% to 77.5±7.2%, P <0.001) from the first to the last quarter of the night in association with a significant decrease in Ptc co 2 (from 42.6±0.9 to 40.8±0.9 mm Hg, P <0.01). Conclusions —In patients with CHF, the shift from OSA to CSA is associated with a reduction in P co 2 . This appears to be related to an overnight deterioration in cardiac function as suggested by the concurrent lengthening of circulation time. Therefore, in CHF patients, alterations in cardiac function may influence apnea type.